2022
DOI: 10.11591/ijphs.v11i1.21245
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression among university students during the lockdown: their protective and risk factors

Abstract: Anxiety and depression among university students were reported to be increased during the outbreak of CoVid-19. Various studies indicated that the phenomenon was triggered by the sudden enforcement of the studying-from-home (SFH) policy. Accordingly, we hypothesized that the students’ online learning efficacy (OLE) predicted the upsurge of the two mental health issues. However, SFH also elevated the students’ inclination towards social media (SM), and it brought further changes in some socio-psychological fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…However, our results indicated that mattering did not significantly predict SWL and it is inconsistent with the previous studies in the same context of Malaysian urbanites amidst the outbreak [31]. It can be explained by the fact that in the Malaysian context, the prolonged social distancing enforcement had increased the levels of anxiety and depression [22], among individuals with lower levels of mattering; which lowered the impact of mattering on their SWL. Regarding the relationship between PSS and PWB, it was suggested that a higher level of PSS predicted lower psychological problems such as depression, anxiety, and stress [14], which translates to better PWB [12], [13].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our results indicated that mattering did not significantly predict SWL and it is inconsistent with the previous studies in the same context of Malaysian urbanites amidst the outbreak [31]. It can be explained by the fact that in the Malaysian context, the prolonged social distancing enforcement had increased the levels of anxiety and depression [22], among individuals with lower levels of mattering; which lowered the impact of mattering on their SWL. Regarding the relationship between PSS and PWB, it was suggested that a higher level of PSS predicted lower psychological problems such as depression, anxiety, and stress [14], which translates to better PWB [12], [13].…”
Section: Discussioncontrasting
confidence: 99%
“…Apart from that, Flett and Heisel [20] also proposed that during this atypical time, mattering was negatively affected due to the restrictions on in-person social interaction. individuals with lower levels of mattering tend to report higher levels of anxiety and depression before the outbreak [21] and during the outbreak [22]. Flett et al [23] and Rashid et al [24] also reported that lower levels of mattering predicted greater suicidal tendencies among university and college students.…”
Section: Introductionmentioning
confidence: 99%
“…Inclination towards the remote online communication, especially in the form of social media predicted higher levels of fear of missing out social feedback (FOMO) of their users [1], [2] and furthermore, they would likely to evaluate themselves in different ways [3]. For instance, before the high inclination towards remote social interaction in social media (pre-COVID/pre-lockdown), people might bump into each other and give each other spontaneous social feedback, such as smiles, nods, hugs, and handshakes [4], [5]; such things would not likely to take place during the pandemic outbreak, as most of the social interaction was conducted online; thus, we would only see the people we have planned to see and discuss about the subjects that we have planned to discuss [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Feelings of low self-esteem are predictors of the onset of depression [7]. The results of the study in Malaysia dan Indonesia stated that the strongest protective factor for depression was social awareness from the environment, while the strongest risk factor for anxiety was the fear of losing [8].…”
Section: Introductionmentioning
confidence: 99%